Non-Power-of-Two FFTs: Exploring the Flexibility of the Montium TP. (2nd September 2009) - van de Burgwal, Marcel D.; Wolkotte, Pascal T.; Smit, Gerard J. M.
Abstract : Coarse-grain reconfigurable architectures, like the Montium TP, have proven to be a very successful approach for low-power and high-performance computation of regular digital signal processing algorithms. This paper presents the implementation of a class of non-power-of-two FFTs to discover the limitations and Flexibility of the Montium TP for less regular algorithms. A non-power-of-two FFT is less regular compared to a traditional power-of-two FFT. The results of the implementation show the processing time, accuracy, energy consumption and Flexibility of the implementation.